Cryptonomicon - Stephenson, Neal (Harper Perennial, 2000)
An American computer hacker operating in Southeast Asia attempts to break a World War II cypher to find the location of a missing shipment of gold. The gold was stolen by the Japanese during the war. Bouncing between World War II and the World Wide Web, Cryptonomicon follows the exploits of Lawrence Waterhouse, a young mathematical genius assigned to a highly secretive outfit that has cracked the fabled Nazi enigma code.